Official and Public Dialogue in Lithuania-Russia Relationships: in Search of Communicative Solutions - N. A. Ivanova (Vestnik MGIMO-Universiteta)
Abstract: Actual Lithuania-Russia relations are characterized as tension. The official rhetoric is strongly negative. The opportunities to maintain public dialogue are restricted, ideas to promote positive cooperation are being criticized by elites and government. Mass-media transmit the official standpoints of the government. Consequently, it works on even more amplification of the public break between the two societies, strengthening discredit, spreading stereotypes and myths about each other. That has been leading to estrangement between the societies of the both countries and also to increase of word outlook, emotional and mental break. In the historical perspective it might become the grand challenge for both states as neighboring countries. However, as in Russia so in Lithuania there are social communities that are interested in developing positive communication even in actual tense circumstances. Thereupon alternative communication platforms, belonging to “soft power” and public diplomacy, become special. The ones that nowadays maintain dialogue in Lithuania-Russia relationships are studied in this article. Besides, the obstacles to a constructive dialogue are revealed. Author gives recommendations on the most effective alternative platforms and “displays”